Aerodynamic Analysis on the Effects of Frontal Deflector on a Truck by using Ansys Software - Varadarajoo, Pavin Kumaar; Ishak, Izuan Amin; Baharol Maji, Daniel Syafiq; Mohd Maruai, Nurshafinaz; Khalid, Amir; Mohamed, Norirda (International Journal of Integrated Engineering, 2022)
Since the early years of the 20th century, when commercial vehicle mass production began, it has been found that air resistance plays a major factor related to vehicle motion. The main causes of aerodynamic drag for automotive vehicles are the flow separation at the rear end of the vehicles. By reducing the drag force, it is possible to increase the fuel economy. Aerodynamic component i.e. Frontal Deflectors (FD) commonly used on trucks to prevent flow separation. Frontal Deflectors themselves do create the drag, but they also reduce drags by preventing flow separation at downstream. The main aim of this paper is to quantify the effect of frontal deflectors on improving trucks aerodynamics. In this study, the simulation ran for 6 different shapes of FD which acquires different height and different placement of FD that is mounted on the truck from the frontal roof by using ANSYS Fluent software. The design of the truck has been done in SOLIDWORK 2018 and the same design is used for analysis in ANSYS (Fluent). The two-equation models used in this study are ð‘˜ âˆ’ ðœ€ with applying the Reynolds-averaged Navier Stokes (RANS) equations for the behaviour of fluid flow around the truck. The Reynolds number used is ð‘…ð‘’ = 1.1 Ã— 106.  Based on the result, all the FDâ€™s resulted in a reduction of coefficient of drag. The drag coefficient of all models differs. The velocity streamline acquired is different between the Frontal Deflector models mounted on the truck and the flow structure and vortex formation differs in various pattern formation. FD 4 produces the least value of drag. Hence, the efficiency of the truck improves. Therefore, FD 4 is the best model as the acquired coefficient of drag is 0.508 with the height (15 mm) and placement of (230 mm) is the best FD to be used on a truck. Consequently, the drag reduction percentage of FD 4 compared to the truck without a FD is 32.2%.